Bioprospecting for amylases, cellulases and xylanases from ericoid associated fungi, their production and characterisation for the bio-economy - Adeoyo, Olusegun Richard (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
South Africa is one of the most productive areas for ericaceous plants with about 850 identified species in the Cape Floral Region. The Albany Centre of Endemism where all fungi used in this study were isolated from, falls within this region. Ericaceous plants interact with some fungi via an association called the ericoid mycorrhizal (ERM) association. All fungi used in this study were isolated from roots of six ericaceous plants; Erica cerinthoides, Erica demissa, Erica chamissonis, Erica glumiflora, Erica caffra and Erica nemorosa. Fungal enzymes are known to play a significant role in the food, brewing, detergent, pharmaceutical and biofuel industries. The enzyme industry is among the major sectors of the world, and additional novel sources are being explored from time to time. This study focussed on amylases (amyloglucosidase, AMG), cellulases (endoglucanase) and xylanases (endo-1,4-P-xylanase) production from ERM fungal isolates. Out of the fifty-one (51), fungal isolates screened, ChemRU330 (Leohumicola sp.), EdRU083 and EdRU002 were among the fungi that had the highest activities of all the enzymes. They were tested for the ability to produce amylases and cellulases under different pH and nutritional conditions that included: carbon sources, nitrogen sources and metal ions, at an optimum temperature of 28Â°C in a modified Melin-Norkrans (MMN) liquid medium. Cellulase specific activity of 3.99, 2.18 and 4.31 (U/mg protein) for isolates EdRU083, EdRU002 and ChemRU330, respectively, was produced at an optimal pH of 5.0. For amylase, ChemRU330 had the highest specific activity of 1.11 U/mg protein while EdRU083 and EdRU02 had a specific activity of 0.80 and 0.92 U/mg protein, respectively, at the same pH with corresponding biomass yield of 113, 125 and 97 mg/50 ml, respectively. Increased enzyme activities and improved mycelial biomass production were obtained in the presence of supplements such as potassium, sodium, glucose, maltose, cellobiose, tryptone and peptone, while NaFe-EDTA and cobalt inhibited enzyme activity. ChemRU330 was selected to determine the consistency and amount of amylase, cellulase and xylanase formed after several in vitro subculturing events. AMG and endo-1,4-P-xylanase were found to have the most consistent production throughout the study period. The AMG was stable at 45oC (pH 5.0), retaining approximately 65% activity over a period of 24 h. The molecular mass of AMG and endo-1,4-P-xylanase were estimated to be 101 kDa and 72 kDa, respectively. The Km and kcat were 0.38 mg/ml and 70 s-1, respectively, using soluble starch (AMG). For endo-1,4-P-xylanase, the Km and Vmax were 0.93 mg/ml and 8.54 U/ml, respectively, using beechwood xylan (endo-1,4-P-xylanase) as substrate. Additionally, crude extracts of five root endophytes with unique morphological characteristics were screened for antibacterial properties and was followed by determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). L. incrustata (ChemRU330) and Chaetomium sp. extracts exhibited varying degrees of inhibition against two Gram-positive and Gram-negative bacteria. The crude extract of L. incrustata was the most effective which was found to inhibit Staphylococcus aureus (MIC: 1 mg/ml), Bacillus subtilis (MIC: 2 mg/ml) and Proteus vulgaris (MIC: 16 mg/ml). The L. incrustata displayed potential for antibacterial production and could be considered as an additional source of new antimicrobial agents in drug and food preservation. Also, the three isolates used for enzyme production were identified to genus and species levels, i.e., Leohumicola incrustata (ChemRU330), Leohumicola sp. (EdRU083) and Oidiodendron sp. (EdRU002) using both ITS and Cox1 DNA regions. The molecular analysis results indicated that these ERM mycorrhizal fungi were similar to those successfully described by some researchers in South Africa and Australia. Therefore, this study opens new opportunities for exploring ERM fungal biomolecules for the bio-economy. The promising physicochemical properties, starch and xylan hydrolysis end- products, and being non-pathogenic make AMG and endo-1,4-P-xylanase potential candidates for future applications as additives in the food industry for the production of glucose, glucose syrups, high-fructose corn syrups, and as well as the production of bioethanol. Finally, the findings of this study revealed that it is possible to produce hydrolytic enzymes from ERM fungi in vitro using chemically defined media.
Keywords: Mycorrhizal fungi; Hydrolases; Ericaceae -- South Africa; Ericaceae Molecular aspects